Historical Awareness Of The Nualain Village Community In Fostering Nationalism Through Baipor Hatama Local Wisdom - Mali, Silvanus Jefrino (Jurnal Indonesia Sosial Sains, 2025)
This research is motivated by the problem of the national perspective of the people in the Indonesia-Timor Leste border region. The objectives to be achieved in this research are to describe the local wisdom of Baipor Hatama, describe and analyze the values contained in the local wisdom of Baipor Hatama which contains historical awareness in fostering nationalism, and describe the activities that emerge from the local wisdom of Baipor Hatama which contains the values of nationalism. The research method used in this research is a case study research method. This research is based on the cultural ties between Indonesia and Timor Leste. The results of this research are first, the community makes Baipor Hatama a symbol of the separation of the tribes in Nualain from those in Timor Leste. Second, the cultural values in the local wisdom of Baipor Hatama and other cultures in the Nualain community can foster nationalism in people in border areas. Third, the historical awareness of the Nualain community is demonstrated by the community's nationalistic attitude by participating in various activities containing nationalist values in the border region.